Age dependency of neurometabolite T1 relaxation times - Murali‐Manohar, Saipavitra; Zöllner, Helge J; Hupfeld, Kathleen E; Song, Yulu; Carter, Emily E; Yedavalli, Vivek; Hui, Steve C. N; Simicic, Dunja; Gudmundson, Aaron T; Simegn, Gizeaddis Lamesgin; Davies‐Jenkins, Christopher W; Oeltzschner, Georg; et al. (Magnetic resonance in medicine, 2025)
Purpose To measure T1 relaxation times of metabolites at 3 T in a healthy aging population and investigate age dependence. Methods A cohort of 101 healthy adults was recruited with approximately 10 male and 10 female participants in each “decade” band: 18 to 29, 30 to 39, 40 to 49, 50 to 59, and 60+ years old. Inversion‐recovery PRESS data (TE/TR: 30/2000 ms) were acquired at 8 inversion times (TIs) (300, 400, 511, 637, 780, 947, 1148, and 1400 ms) from voxels in white‐matter‐rich centrum semiovale (CSO) and gray‐matter‐rich posterior cingulate cortex (PCC). Modeling of TI‐series spectra was performed in Osprey 2.5.0. Quantified metabolite amplitudes for total N‐acetylaspartate (tNAA2.0), total creatine at 3.0 ppm (tCr3.0), and 3.9 ppm (tCr3.9), total choline (tCho), myo‐inositol (mI), and the sum of glutamine and glutamate (Glx) were modeled to calculate T1 relaxation times of metabolites. Results T1 relaxation times of tNAA2.0 in CSO and tNAA2.0, tCr3.0, mI, and Glx in PCC decreased with age. These correlations remained significant when controlling for cortical atrophy. T1 relaxation times were significantly different between PCC and CSO for all metabolites except tCr3.0. We also propose linear models for predicting metabolite T1s at 3 T to be used in future aging studies. Conclusion Metabolite T1 relaxation times change significantly with age, an effect that will be important to consider for accurate quantitative MRS, particularly in studies of aging.